Service quality, customer satisfaction and service loyalty in retail banking sector in Thailand & Malaysia : an exploratory research on validity and critical factor - Chuen, Seong Ooi (Prince of Songkla University, 2014)
Thesis (M.B.A., (Business Administration))--Prince of Songkla University, 2013